Bioethics & the brain. - Foster, K.R (IEEE spectrum)
Microelectronics and medical imaging are bringing us closer to a world where mind reading is possible and blindness banished - but we may not want to live there. New ways of imaging the human brain and new developments in microelectronics are providing unprecedented capabilities for monitoring the brain in real time and even for controlling brain function. The technologies are novel, but some of the questions that they will raise are not. Electrical activity in the brain can reveal the contents of a person's memory. New imaging techniques might allow physician to detect devastating diseases long before those diseases become clinically apparent. And researchers may one day find brain activity that correlates with behavior patterns such as tendencies toward alcoholism, aggression, pedophilia, or racism. But how reliable will the information be, how should it be used, and what will it do to our notion of privacy? Meanwhile, microelectronics is making access to the brain a two-way street. The same electrical stimulation technologies that allow some deaf people to hear could be fashioned to control behavior as well. What are the appropriate limits to the use of this technology? Ethicists are only now beginning to take note of these developments in neuroscience.